Program IPTEK bagi Inovasi dan Kreatifitas Kampus IT Training & Service Center (ITSC) UNIKOM - Budi Herdiana; Bobi Kurniawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The community of society is one of main activities required by a lecture as part of the tri dharma which aimed to apply and implement the scientific competence a lecturer to contribute positively especially for society needs. It activities do in UNIKOM is a form of the creativity between lecturers and students who want to develop their skill especially in information technology and entrepreneurship knowlegde, and therefore we established a business unit in 2014 was named